Pengaruh Pengungkapan ESG (Environmental, Social, and Governance) terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Pemoderasi - Dzakiyani, Hanifa Taradz (Jurnal EMT KITA, 2026)
The instability of firm value, along with the growing global attention to sustainability issues, has positioned ESG (Environmental, Social, and Governance) disclosure as a crucial component of long-term business strategy. This study aims to examine the effect of ESG disclosure on firm value, with financial performance as a moderating variable, focusing on companies in the energy sector. The research objects are energy companies listed on the Indonesia Stock Exchange during 2021–2024. The sample was selected using a purposive sampling method, resulting in a total of 32 companies per year that met the criteria. Data were analyzed using the MRA (Moderated Regression Analysis) technique with the assistance of SPSS version 29. The findings indicate that ESG disclosure has a negative effect on firm value and financial performance significantly moderates this relationship by weakening the negative impact of ESG disclosure. These findings highlight that ESG disclosure alone is not sufficient to enhance firm value unless it is accompanied by strong financial performance. Therefore, a synergy between sustainability efforts and financial performance is essential for building sustainable firm value and serves as an important reference for investors in making investment decisions.